MANFAAT PRASASTI BAGI PENULISAN SEJARAH LOKAL - Djoko Dwiyanto (Berkala Arkeologi, 1998)
Among the various sources of ancient historical writing, inscriptions are in the top rank, because inscriptions were written at the same time as the events. Even so, not much can be revealed from the inscription and vice versa, the inscription cannot provide complete or comprehensive information about one aspect. Therefore, the use of inscriptions as historical sources must go through a procedure called interpretation.